A Study on prevalence of detofacial anomalies in 12 to 14 years old students inTehran - Rashidi Birgani M; Ravanmehr H (Tehran University of Medical Sciences, 1998)
The purpose of this study was to determine the prevalence of dentofacial anomalies in 12 to 14 years old students in Tehran."nThe sample consisted of 500 students. 250 of them were females and 250 were males. The evaluation of saggital skeletal relationships revealed tha 16% of samples had normal occlusion, 48% of them had CI I malocclusion, 15,6% had CI II Div I malocclusion, 12% of them had CI HI malocclnsion, 5.2% of them had CI. II Div 2 malocclusion and 3.2% of them had pseudo CI III malocclusion. The prevalence of other dentofacial anomalies obtained in this study are, crowding 40.6%, deepbite 27.2%, spacing 20.6%, mandibular deviation 19.4%, unilateral posterior crossbite 9.2%, anterior openbite 6.6%, posterior openbite 5.6%, asymmetry 1.6% and bilateral posterior crossbite 1.6%. The prevalence of dental anomalies in the sample population was as follws: rotated teeth 13.4%, malposed teeth 12.2%, teeth with large size 3.2%, malshaped teeth 2.4% and teeth with smal size 2%. A part from determining the total values mentioned, the prevalence of saggital relationships oral dentofacial anomalies was assessed separately in each of the female and the male samples.